Applicability of Demirjian and Chaillet’s methods in estimating dental age in children from the state of Zulia, Venezuela - Ortega-Pertuz, Ana Isabel; Espina-Fereira, Ángela Irene; Fereira-Paz, José Luis (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: dental age (DA) is used in clinical disciplines to evaluate whether an individual is advanced or delayed in his or her dental development, or to determine the age of living or deceased subjects with no valid identification documents; it is also useful in forensic practice. Objective: to study the applicability of the methods of Demirjian et al (revised, 1976) and Chaillet et al in estimating DA in a sample of Venezuelan children and adolescents. Methods: a descriptive, retrospective field study in 516 panoramic X-rays of patients of both sexes with chronological ages ranging from 6 to 18 years. Dental development was assessed in the seven lower left teeth using the maturation stages proposed in the method of Demirjian et al, while DA calculation was carried out according to the reference tables provided by each method. Descriptive statistics were obtained, as well as mean differences between chronological age (CA) and DA estimated by a Student’s test. Results: age overestimation was observed using Demirjian’s method up to the age of 15 years, as well as age underestimation with Chaillet’s method. Considering the total sample, both methods underestimated age (Demirjian 0.20 ± 1.46; Chaillet 0.34 ± 1.39), and the difference between CA and DA was significant (Demirjian p = 0.0002; Chaillet p = 0.000). Conclusions: both methods can be used in the sample studied, considering that DA should be assessed in conjunction with other indicators of maturation to evaluate the development of an individual.